Futures and Forwards Contracts from Perspective of Islamic Law - Ehab M. M. Injadat (Journal of Economics and Political Economy, 2014)
Futures and forwards contracts are considered of the main derivatives contracts, which offer many services and benefits, namely risk management (hedging), and speculation. However, these contracts from the perspective of Islamic experts are varying and non-uniformed, where there are those who see futures and forwards contracts as unacceptable and forbidden by Islamic law, and there are also those who see futures and forward contracts as acceptable and compatible with Islamic law. This paper attempts to clarify the Islamic law perspective of futures and forwards contracts, to give a clearer picture about the legitimacy of these contracts, in order to examine whether the using of futures and forwards contracts are permissible or prohibited. The study follows the inductive method and descriptive research by displaying texts, previous literature, opinions of futures and forwards contracts from Islamic law perspective and comparisons between them, including the balancing and elicitation in light of Islamic law standards, strength of the arguments relied upon by each party and commitment to offer the presentation matter scientifically. The study's conclusion the current application of futures and forwards contracts in the financial markets are impermissible and are considered prohibited contracts. The study find futures and forwards contracts contain a number of forbidden elements in Islamic law, especially gambling and harm speculation additions to a number of pictures of some forbidden elements such as gharar (ambiguity), riba (usury) that are still in the circle of debate among Muslim scholars. However, the availability of a some terms and conditions that can dispose the prohibited elements in these contracts may make them compatible and consistent with the Islamic law.
Keywords: G10; G13; G15; 330; Derivatives; Forward; Islamic law; Hedging